Prevalence and associated factors of microbial water quality from drinking water in Ethiopia: A systematic review and meta-analysis protocol. - Asmamaw Deguale Worku; Bezatu Mengistie Alemu (PLoS ONE)
Purpose To determine the pooled prevalence and associated contributing factors of microbial water quality, especially the most recent fecal contamination indicator, fecal coliforms, from drinking water in Ethiopia. Method The review will be conducted per the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines and PRISMA-P and registered in PROSPERO CRD42024537804. The studies will be identified from peer-reviewed literature, grey literature, and expert submissions. To identify peer-reviewed literature, "microbial water quality" will be combined with terms to restrict the search for drinking water and measure the prevalence and/or associated factors of microbial water quality. We further restricted the search in Ethiopia. The following databases will be used: PubMed/MEDLINE, Google Scholar, Worldwide Science, and Science Direct. Two independent reviewers will identify studies, extract data, assess the risk of bias, and assess methodological quality. The studies included will be determined in terms of quality based on the criteria listed in the Goanna Bridge Institute quality parameters. Statistical techniques like Higgins I2 will be used to investigate heterogeneity among the included studies. Sensitivity and subgroup analysis will be carried out to evaluate how reliable the results are. A funnel plot will be used to evaluate reporting publication bias, and Begg's and Egger's assessments will be used to check funnel plot balances. Discussion This review and meta-analysis will thoroughly discover and integrate the data available on the prevalence and associated factors of fecal coliforms contamination in drinking water. The findings from this systematic review and meta-analysis will be compared and discussed with those from other studies. Conclusion Our systematic review and meta-analysis will help to develop specific recommendations for identified fecal coliforms contamination and associated factors in drinking water in Ethiopia. Moreover, this study will identify research gaps and guide future research and public health measures.